2003
DOI: 10.1002/cyto.b.10064
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric quantitation of red blood cell vesicles in thalassemia

Abstract: Background: Thalassemia is a hereditary hemolytic anemia caused by mutations in the globin gene complex. Circulatory disturbances including arterial and venous thrombosis have also been noted in these patients. Aggregability of abnormal RBC and the high level of membrane-derived microparticles stemming from activated platelets and other blood cells are thought to be responsible for the associated thrombotic risk. Destruction of RBC is also thought to be an important pathophysiological consequence, particularly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 39 publications
(55 reference statements)
1
78
1
1
Order By: Relevance
“…The vesicles contained Hb but were almost completely devoid of the membrane cytoskeletal polypeptides, spectrin, ankyrin and band 4AE1. We, and others, have reported that circulating vesicle levels are also observed in patients with other haemolytic anaemias (Wagner et al, 1986;Setty et al, 2000;Westerman et al, 2002;Pattanapanyasat et al, 2004). The effects of vesiculation include loss of RBC surface area and microspherocyte formation (Allan et al, 1982), and simulates the vesiculation observed in senescent and apoptotic normal cells .…”
mentioning
confidence: 66%
“…The vesicles contained Hb but were almost completely devoid of the membrane cytoskeletal polypeptides, spectrin, ankyrin and band 4AE1. We, and others, have reported that circulating vesicle levels are also observed in patients with other haemolytic anaemias (Wagner et al, 1986;Setty et al, 2000;Westerman et al, 2002;Pattanapanyasat et al, 2004). The effects of vesiculation include loss of RBC surface area and microspherocyte formation (Allan et al, 1982), and simulates the vesiculation observed in senescent and apoptotic normal cells .…”
mentioning
confidence: 66%
“…The MP in plasma were analyzed by flow cytometry using a modification of a previously described method: 22 25 μL of plasma diluted 1:1 with PBS-glucose 5mM were analyzed using anti-CD41 (BD, Franklin Lakes, NJ, USA) and anti-glycophorin-A (Dako, Denmark), both diluted 1:10.…”
Section: Analysis Of Microparticlesmentioning
confidence: 99%
“…Informed consent was provided according to the Declaration of Helsinki. Complete blood cell count (Cell-Dyn 370, Abbott Diagnostics) and serum level of LDH were obtained by routine methods (Cobas, Roche); LDH isoenzymes by electrophoresis on agarose gel and specific enzymatic revelations (Interlab G26); plasma-Hb determination by spectrophotometry; erythrocytederived microvesicles by flow cytometry (FACSCalibur, BD Biosciences) 7 ; and haptoglobin by immunoturbidimetry (Olympus AU 640 system). Kruskal-Wallis and Spearman correlation tests were performed using GraphPad Prism 5 (GraphPad Software Inc.).…”
mentioning
confidence: 99%